The Effects of Magnetically Treated Water on the Performance and Immune System of Broiler Chickens - Al-Mufarrej, S.; Al-Batshan, H.A.; Shalaby, M.I.; Shafey, T.M. (International Journal of Poultry Science, 2005)
The effects of water treatment (tab water (CTW) vs. magnetically treated water (MTW)) on the performance (body weight gain, feed intake, feed conversion ratio (feed/gain)) from day to 32 days of age, water consumption (WC) and Water: feed consumption ratio (WFR) during the first three weeks of age (starter phase), carcass composition at 32 days of age, and antibody responses to SRBS antigens of sexed broiler chickens were investigated. MTW was prepared by exposing the water to a magnetic field of approximately 500 gauss. The exposure of water to the magnetic field slightly increased the pH of water from 7.72 to 7.86. The water treatment influenced WC of birds. The daily WC of birds on the MTW was significantly (P